DEM of the Central Kentucky Karst Region, USA - Rachel Bosch (PANGAEA, 2020)
This DEM is the result of merging the data, using QGIS, from 1472 tiles of 5-foot resolution lidar-derived DEMs downloaded from https://kygeonet.maps.arcgis.com/home/webmap/viewer.html?webmap=785e6040154e4050bda80049fc12d4a6.